Improvement of Student Geography Learning Achievement Trough Application of Coperative Learning Model Type â€œNumbered Head Togetherâ€ in X Grade SMAN 2 Watansoppeng - Hariana, Hilda Cahyani (Universitas Negeri Makassar, 2018)
This study aimed to assess whether NHT cooperative learning model to improve learning outcomes of students geography. Implementation of the actions performed by 2 cycles, each cycle consists of planning, action, observation and evaluation, and reflection. Analysis using quantitative descriptive analysis. The results showed that: there is an increase in learning outcomes for implementing cooperative learning model NHT during the execution of the learning cycle I and xycle II. The everage value of the learning outcomes before deploying cooperative learning model NHT increased 68,09 after applied cooperative learning model NHT, in the first cycle is obtained mean values obtained by an average of 76,26. It can be concluded that through the application of learning models on the subjects geography of NHT can improve student learning outcomes geography class X2 SMAN 2 Watansoppeng.Penelitian ini bertujuan untuk mengkaji apakah model pembelajaran kooperatif tipe NHT dapat meningkatkan hasil belajar geografi siswa.Â Pelaksanaan tindakan yang dilakukan sebanyak 2 siklus, tiap siklus terdiri dari tahap perencanaan, pelaksanaan tindakan, observasi dan evaluasi dan refleksi. Teknik analisis data menggunakan analisis deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa: ada peningkatan hasil belajar selama menerapkan model pembelajaran kooperatif tipe NHT selama pelaksanaan pembelajaran siklus I dan siklus II. Nilai rerata hasil belajar siswa yang sebelum diterapakan model pembelajaran kooperatif tipe NHT 68,09 meningkat sesudah diterapkan model pembelajaran kooperatif tipe NHT, pada siklus I diperoleh nilai rerata 69,74 dan Pada siklus II diperoleh nilai rerata sebesar 76,26.Dengan demikian dapat disimpulkan bahwa melalui penerapan model pembelajaran NHT pada mata pelajaran geografiÂ dapat meningkatkan hasil belajar geografi siswa kelas X2 SMA Negeri 2 Watansoppeng.